Does microcredit increase aspirational hope? Evidence from a group lending scheme in Sierra Leone. (April 2020) - Garcia, Adriana; Lensink, Robert; Voors, Maarten
Highlights: Microcredit helps to achieve the Sustainable Development Goals. We look at internal constraints such as aspirational hope. Microcredit is associated with both aspirational hope and economic welfare. Social connectedness and exposure to role models links microcredit to aspirations. Abstract: Microcredit has received considerable attention due to its potential to help achieve the Sustainable Development Goals (SDGs), in particular through its effects on poverty alleviation, female empowerment and self-employment. To date, its effectiveness has largely been evaluated in terms of relieving external constraints of the poor, such as a lack of financial capital for business development. The current study examines whether, and to what extent, microcredit can change internal constraints, such as aspirational hope. We use a cross-sectional dataset of 1295 women in Sierra Leone, 854 of whom are active borrowers of a Microfinance Institution, BRAC. To assess the relationship between microcredit, aspirational hope and economic welfare, we rely on BRAC's eligibility criteria, that only allow access to finance for women living with-in 4 km of a BRAC branch. We find statistically significant and economically meaningful positive associations with both aspirational hope and economic welfare. Overall, this study suggests that microcredit could play an important role in reducing internal psychological constraints, and via this channel contributes to the realization of the SDGs.